Perception and Facts Regarding Electroconvulsive Therapy at Benazir Bhutto Hospital, Rawalpindi - Rao, Muhammad Azeem; Minhas, Fareed Aslam; Tasleem, Shumaila; Zaidi, Syed Rafay Hussain; Najeeb, Bahjat; Ali, Manzoor (Journal of Rawalpindi Medical College, 2023)
Objective: This study delves into the effectiveness of Electroconvulsive Therapy (ECT) as a treatment for psychiatric disorders, focusing on its administration protocols, patient demographics, and therapeutic outcomes. Methods: The research, conducted at Benazir Bhutto Hospital, Rawalpindi, from 2013 to 2018, analysed data from 1779 patients, revealing a substantial prevalence of bipolar affective disorder, severe depressive illness, postpartum psychosis, and catatonic schizophrenia among those undergoing ECT. Results: The study underscores the rapid therapeutic response observed within 1 to 5 ECT sessions, emphasizing the expeditious nature of ECT. The absence of serious side effects reported during the study period supports the safety profile of ECT when administered under appropriate protocols. Conclusion: Electroconvulsive Therapy (ECT) is a viable and effective treatment modality for various psychiatric disorders. This research contributes valuable insights into the utilization and outcomes of ECT, it acknowledges the need for future investigations to explore patient experiences, long-term follow-ups, and potential side effects. Keywords: electroconvulsive therapy, psychiatric illness.